Recent advances in RF-LDMOS high-power IC development - Burger, W.R. (2009 IEEE International Conference on IC Design and Technology, 2009)
RF-LDMOS is the dominant RF power device technology in the infrastructure market from cellular through WiMAX frequencies. High performance, low cost, and excellent reliability are just a few of the factors responsible for this dominant position. Base station suppliers and their customers continue to demand improvements in system efficiency while simultaneously providing lower cost solutions. RF-LDMOS continues to evolve to meet these demanding requirements. One key evolution that provides improved performance while lowering cost is the introduction of high power RFICs. By combining high Q integrated passives with RF-LDMOS device technology, multi-stage, high-power (>100 W) devices can be realized that offer superior performance and lower cost than the corresponding discrete transistor implementation can provide, with similar if not superior reliability. This paper will review recent RF-LDMOS high-power IC developments.